2001
DOI: 10.1524/ract.2001.89.6.393
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Th(IV) and Eu(III) by α-isosaccharinic acid under alkaline conditions

Abstract: The complexation of Th(IV) and Eu(III) by α-isosaccharinic acid (ISA) has been studied in the pH range from 10.7 to 13.3 by batch sorption experiments, and the influence of Ca on the complexation was investigated. Sixteen data sets -each determined at variable ISA concentrationsare used to determine the stoichiometry of the complexation reactions and the stability constants. Based on best-fit analysis of the sorption data, it is postulated that 1:1 Th:ISA complexes are formed in the absence of Ca according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 21 publications
(42 reference statements)
2
60
2
Order By: Relevance
“…A cation exchange resin Bio-Rad 50W-X2 (Bio-Rad Laboratories, Hercules, USA) was used as sorbent material. Before use, this resin was washed and conditioned following a procedure described elsewhere [4]. Gluconic acid was available as a Na salt (Merck AG, Dietikon, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A cation exchange resin Bio-Rad 50W-X2 (Bio-Rad Laboratories, Hercules, USA) was used as sorbent material. Before use, this resin was washed and conditioned following a procedure described elsewhere [4]. Gluconic acid was available as a Na salt (Merck AG, Dietikon, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…This wall sorption has been previously shown to depend on the complexation with organic ligands such as GLU [4]. Therefore, in order to evaluate the sorption of 239 Np on the tubes walls, the centrifuge tubes were emptied after sampling, rapidly rinsed with 10 mL of a solution identical to the one used in the preceding sorption test but without 239 Np tracer and then filled with 20 mL 1 M HCl solution to allow desorption of the radionuclide from the walls.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Only very limited reliable data are available for isosaccharinate (ISA -) complexes of thorium. Two types of data that are available for this system are 1) those that are based on sorption experiments under alkaline conditions [2][3][4][5][6] and 2) those based on liquid-liquid extractions [7,8]. The data based on sorption experiments have recently been reviewed by Hummel et al [1] who concluded that the entire data can be represented by [Th(OH) 4 (aq) + ISA -= Th(OH) 4-x (ISA -xH ) +xH 2 O; Th(OH) 4 (aq) + 2ISA -+ Ca 2+ = CaTh(OH) 4-2y (ISA -yH )(aq) + 2yH 2 O] and that the values of x and y in the above reactions cannot be determined by standard thermodynamic methods.…”
Section: Introductionmentioning
confidence: 99%